DEVELOPMENT OF E-MODULE BASED ON CONTEXTUAL APPROACHES ON WORK AND SIMPLE MACHINES FOR SECONDARY SCHOOL - Annisa Efendi; Yurnetti Yurnetti (Pendidikan IPA, FMIPA, UNP, 2021)
The education system is required to be able to follow the development of science and technology to prepare a generation that is ready to deal with the challenges of this era. The current curriculum is curriculum 2013. In curriculum 2013 students are required to be active and able to learn independently. The procurement of teaching materials at SMP Negeri 7 Padang is considered not to be able to support independent learning, especially during this online learning period. This study aims to produce science e-module for SMP/MTs based on a contextual approach on work and simple machines to valid and practical. Type of research is Research and Development (R&D) using the Plomp model which consists of three stages, namely the preliminary research, the prototyping stage, and the assessment phase. The research subjects were 3 lecturers of Science Education, FMIPA UNP, teachers and students of SMP Negeri 7 Padang. The instrument used is a questionnaire of validity and practicality. The research data is processed using the kappa moment formula. Based on the results of data analysis, the results of the validity test, the results of the practicality test based on the teacher's response, and the practicality test based on the student's responses were 0.85, 0.87, and 0.83 with very high category. It can be concluded that the e-module for SMP/MTs based on a contextual approach on work and simple machines has been valid and practical for use in class VIII SMP/MTs.